DIMENSI PERILAKU RASIONAL EKONOMI MASYARAKAT MELAYU MEMPAWAH - Manja Pratanti; Muhammad Basri; Heni Kuswanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research was conducted on The Malay community of Mempawah. The purpose ofthe research was to know the people's rational behavior among the community on someaspects such as tradeoff, opportunity cost, marginalism, and incentive. This researchwas qualitative with the phenomenological approach. The samples were 14 peopletaken using the snowball sampling technique. Based on the result, the aspect of tradeoffoccurred in some cases such as the consideration of participation on robo-robo andbuang-buang, the gift selection in the wedding party, and the yarn's option for kaintenun awan berarak. In the robo-robo, the opportunity cost was the cost of sound systemrental. The cost determination was the opportunity cost of the wedding party, and theopportunity cost of kain tenun awan berararak was the cost of the yarn. Themarginalism aspect, for robo-robo the aspect was the additional cost of sound systemrental, in the wedding party was the increased cost on the box rental and the purchaseof toana tools. The incentive aspect of robo-robo was on the economic improvement for society. The incentive of wedding party was on tarop's making, and kain tenun awanberarak was the participation in the training as the reward.Keywords: Incentive, Marginalism, Opportunity Cost, Tradeoff.